Diffuse coronary artery ectasia in a patient with left main coronary artery trifurcation - Wasilewski, Jarosław; Desperak, Piotr; Bujak, Kamil; Głowacki, Jan; Gąsior, Mariusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
The term coronary ectasia is reserved to describe a diffuse dilatation of coronary artery segments that have a diameter that exceeds the size of normal adjacent coronary segments by 1.5 times. The occurrence of coronary artery ectasia (CAE) ranges from 3% to 8% in the group of patients undergoing coronary computed tomography angiography. The CAE is associated with traditional risk factors and often co-exists with coronary atherosclerosis, which suggests that ectasia may represent an advanced form of atherosclerosis. Nevertheless, there is a lack of consensus on the clinical implications and management of patients in whom the occurrence of CAE is observed, especially in patients without concomitant obstructive atherosclerosis. Here, we present a rare case of a 62-year-old patient with multiple CAEs and left main trifurcation.